Using Cu–Zn–Sn–O Precursor to Optimize CZTSSe Thin Films Fabricated by Se Doping With CZTS Thin Films - Li, Qian; Hu, Jinpeng; Cui, Yaru; Wang, Juan; Hao, Yu; Shen, Tong; Duan, Lizhen (Frontiers in Chemistry, 2021)
The copper-zinc-tin oxide(CZTO) precursor was synthesized to avoid sudden volume expansion from CZTO precursor to Cu2ZnSnS4(CZTS) thin film and smooth CZTSSe thin film surfaces without pinholes. The copper-zinc-tin oxide(CZTO) precursor was prepared by co-precipitation and ball milling to form nano ink of copper-zinc-tin oxide(CZTO). Based on the copper-zinc-tin oxide(CZTO) precursor, the CZTS thin film was fabricated and then selenized to make pinhole-free and flat Cu2ZnSn(S,Se)4(CZTSSe) thin film. The results show that the copper-zinc-tin oxide(CZTO) precursor greatly contributed to elevate the homologous surface characteristics and crystallinity of CZTSSe thin films by controlling selenium temperature, selenium time and selenium source temperature. Finally, the conversion efficiency of CZTSSe thin film solar cell fabricated from copper-zinc-tin oxide(CZTO) precursor was 4.11%, with an open circuit voltage (Voc) of 623 mV, a short circuit current density (Jsc) of 16.02 mA cm-2 and a fill factor (FF) of 41.2%.